If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -26 = 34 + -10x Reorder the terms: -26 + -8x = 34 + -10x Solving -26 + -8x = 34 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -26 + -8x + 10x = 34 + -10x + 10x Combine like terms: -8x + 10x = 2x -26 + 2x = 34 + -10x + 10x Combine like terms: -10x + 10x = 0 -26 + 2x = 34 + 0 -26 + 2x = 34 Add '26' to each side of the equation. -26 + 26 + 2x = 34 + 26 Combine like terms: -26 + 26 = 0 0 + 2x = 34 + 26 2x = 34 + 26 Combine like terms: 34 + 26 = 60 2x = 60 Divide each side by '2'. x = 30 Simplifying x = 30
| 11x+42=9 | | .333(27x-18)=-12 | | -82+3x=86+10x | | 9x^3-40=0 | | 7(4-h)=3h | | 8(-1)-1=9(-1) | | x*lnx+5*lnx=0 | | x-9/x-9 | | 2x(x+1)-30=30 | | 4/z=12/15 | | -4x-20=16-7x | | 5x-85=123-3x | | -14+10x=18+8x | | -4(x-8)=-20 | | 3/5=x/22 | | 3(5x-7)=25 | | 2x+4+6=x+14+1 | | 4x^2-16x+2.5=0 | | 8/9(x-1)=16 | | -3(x-5)-30=3 | | 8(2x+5)=6(x+10) | | n=r/2 | | 5(12x+2)=60x-3 | | 1.8+2.8=2.5+21 | | 8k^2+1=65 | | 7(3y-2)-(9y+5)= | | -30-10x=-12x+28 | | 3/10x=-15 | | -6=-(x-20) | | 12=-6-3/4x | | cosx=-0.09 | | 28x=7(10-x) |